An insight into thermal and vibration cyclic energy harvesting using ferroelectric ceramics. Issue 168 (2nd January 2016) - Vats, Gaurav; Patel, Satyanarayan; Vaish, Rahul
Abstract : This article reviews the basics of ferroelectric energy harvesting cycles based on thermal fluctuation and mechanical confinement. In this context, five cycles (Olsen cycle, Clamped Olsen cycle, Electro-Mechanical cycle, Thermally Biased Electro-Mechanical cycle and New Power cycle) are studied for two different compositions (0.94Bi1/2 Na1/2 TiO3 –0.06BaTiO3 : BNT–6BT; 0.91(Bi1/2 Na1/2 )TiO3 –0.07BaTiO3 –0.02K0.5 Na0.5 NbO3 : BNT-BT-KNN;) which represents two distinct classes (based on domain wall rotation/motion) of ferroelectric materials. These can be classified as the composition with dominating impact of mechanical forces while the other is with ascendant thermal effects over the domain wall behavior.